KEBIJAKAN PENANGANAN OVERCROWDING (KELEBIHAN KAPASITAS) DI RUMAH TAHANAN NEGARA KELAS I MAKASSAR PERSPEKTIF SIYASAH SYAR’IYYAH - Fitrah, Yuska; Arbani, Tri Suhendra (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
The purpose of this research is to find out how the policy of handling overcrowding (excess capacity) in the Makassar class I state detention house, how the impact of handling overcrowding (excess capacity) for detainees and prisoners, and handling overcrowding (excess capacity) in the perspective of siyasah syar'iyyah. This type of research is empirical research with juridical and normative syar'i approaches. Data collection techniques through observation, interviews, and documentation. The results of this study indicate that the handling of overcrowding (excess capacity) at the Makassar Class I State Prison is carried out by the assimilation program, granting conditional leave and parole, remission and redistribution or transfer of prisoners. While the impact of handling overcrowding (overcapacity) for detainees and prisoners at the Makassar Class I State Detention Center, namely, reducing the negative things caused by overcrowding (overcapacity), such as maximizing the provision of health services by officers, lack of peinyakiit meinular between narapiidana and prisoners, and habitation rooms in accordance with the capacity that should be sympathized. The handling of overcrowding (excess capacity) issued by the government to reduce the number of prisoners and detainees in each prison and detention center is in accordance with the concept of siyasah shar'iyyah, which is to bring good (maslahah) and reject destruction (mafsadat). Handling overcrowding (excess capacity) is carried out as an effort to reduce the negative impact of overcrowding conditions (excess capacity).